Fischler on CAP reform and the EU position in the WTO - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Speaking at the FAO ministerial meeting in Rome on December 1 st 2003 the...